Intrathecal Injection of miR-133b-3p or miR-143-3p Prevents the Development of Persistent Cold and Mechanical Allodynia Following a Peripheral Nerve Injury in Rats. (21st August 2018) - Norcini, Monica; Choi, Daniel; Lu, Helen; Cano, Mercedes; Piskoun, Boris; Hurtado, Alicia; Sideris, Alexandra; Blanck, Thomas J.J.; Recio-Pinto, Esperanza
Highlights: LV-miR-133 or LV-miR-143 immediately after injury prevents chronic pain, and 3 days after injury they had partial effects. LV-miR-1 immediately after or 3 days after nerve injury has no effect on neuropathic pain. MiR-133-3p and miR-143-3p, but not miR-1-3p, enhance the KCl-evoked cytoplasmic Ca 2+ increase. With 3′UTR-Scn2b or 3′UTR-TRPM8: miR-133-3p and miR-143-3p reduced the expression of the reporter gene. LV-miR-133 and LV-miR-143 reduced mRNA for Scn2b, Piezo2, and TRPM8. LV-miR-1 reduced mRNA for Scn2b and Piezo2. Abstract: In DRG an increase in miR-133b-3p, miR-143-3p, and miR-1-3p correlates with the lack of development of neuropathic pain following a peripheral nerve injury. Using lentiviral (LV) vectors we found that a single injection of LV-miR-133b-3p or LV-miR-143-3p immediately after a peripheral nerve injury prevented the development of sustained mechanical and cold allodynia. Injection of LV-miR-133b-3p or LV-miR-143-3p by themselves or in combination, on day 3 post-injury produced a partial and transient reduction in mechanical allodynia and a sustained decrease in cold allodynia. Injection of LV-miR-1-3p has no effect. Co-injection of LV-miR-1a with miR-133b-3p or miR-143-3p on day 3 post-injury produced a sustained decrease in mechanical and cold allodynia. In DRG cultures, miR-133b-3p and miR-143-3p but not miR-1-3p, enhanced the depolarization-evoked cytoplasmic calcium increase. Using 3′UTR target clones containing a Gaussian luciferase reporter gene we found that with the 3′UTR-Scn2b, miR-133-3p and miR-143-3p reduced the expression while miR-1-3p enhanced the expression of the reporter gene. With the 3′UTR-TRPM8, miR-133-3p and miR-143-3p reduced the expression and miR-1-3p had no effect. With the 3′UTR-Piezo2, miR-133-3p increased the expression while miR-143-3p and miR-1-3p had no effect. LV-miR133b-3p, LV-miR-143-3p and LV-miR1a-3p reduced Scn2b-mRNA and Piezo2-mRNA. LV-miR133b-3p and LV-miR-143-3p reduced TRPM8-mRNA. LV-miR-133b-3p and LV-miR-143-3p prevent the development of chronic pain when injected immediately after the injury, but are only partially effective when injected at later times. LV-miR-1a-3p had no effect on pain, but complemented the actions of LV-miR-133b-3p or LV-miR-143-3p resulting in a sustained reversal of pain when co-injected 3 days following nerve injury.